Audit of Surgical management and outcome of colorectal cancer at B.P.KI.H.S., Eastern Hospital of Nepal: an institutional review - Sah, Suresh Prasad; Gupta, Rakesh Kumar; Karkee, Rikesh Jung; Gupta, Mukesh Kumar; Paudel, Poonam (International Surgery Journal, 2018)
Background: Colorectal cancers (CRCs) are the third most commonly diagnosed cancer in human and major public health problems worldwide. The number of people afflicted with cancer is increasing in the country, and if the trend continues, cancer could soon be among Nepal’s main killer diseases. The purpose of this study was to know the management and outcome of colorectal surgery for colorectal cancer at our centre. Methods: The study was conducted in the Department of Surgery, B.P.K.I.H.S. Dharan, after ethical approval from institutional ethical review board. All patients of colorectal cancer who were operated in our hospital, between 15th June 2012-15th June 2017 (5 years) were included in this study. Each patient’s medical record was reviewed retrospectively. Data on the patients presenting complaints, disease status, radiological findings, treatments provided, co morbidities, operative details, postoperative mortality and morbidity, histological results, outcomes and follow up was retrieved from the available case record files and was recorded in predesigned performa. Only histopathological confirmed cases were included in the study. Results: Total of 109 patients of colorectal carcinoma was registered in our hospital in last five years but only 69 patients underwent curative colorectal surgery at our centre. Out of 69 patients, 41(59.42%) were male and 28(40.58%) were females. The range of the age was 22 to 86; the median age at the diagnosis was 56.5 years. Out of 69 patients, 19 patients underwent right sided hemicolectomy, 12 patients underwent left sided hemicolectomy, 29 patients underwent anterior resection (high/low) and 9 patients underwent abdominoperineal resection. About 95.42% cases were adenocarcinoma on histology. The overall morbidity and mortality were 21.52% and 8.45% respectively. Conclusions: Colorectal cancer is common cancer and there is increasing trend. We believes that until and unless a population-based cancer registry is created and maintained, it will be difficult to project the exact number of people living with colorectal cancer and the necessary measures to be taken.